Increasing Production Efficiency in Handicraft Small Industries in West Java Through the Utilization of Technological Innovation - Putra, Alfa Santoso Budiwidjojo; Wibowo, Teguh Setiawan (Westscience Press, 2023)
This study looks at the dynamics of technical innovation adoption and how it affects the productivity of small-scale craft businesses in West Java, Indonesia. A quantitative approach was used to collect data from 110 small craft businesses, including statistical analysis and quantitative surveys. The workforce had high skill levels, moderate levels of technology adoption, and perceived problems such as resistance to change and financial restrictions. These findings were supported by descriptive statistics. Technology use, worker skills, and production efficiency were found to be significantly positively correlated, as evidenced by multiple regression analysis. Differences in adoption patterns between rural and urban industries were revealed through cross tabulation. The results of this study highlight the need for a customized approach, resource distribution and information exchange to enhance technical innovation in the heterogeneous craft industry in West Java.